Perinatal prognosis in euploid fetus with cystic hygroma. Report of two clinical cases - Rafael Eduardo Tarazona-Bueno; Rafael Leonardo Aragón-Mendoza; Deisy Yurany Daza Leguizamón; Marcela Altman-Restrepo (Case Reports)
Introduction: Cystic hygroma (CH) is a rare congenital anomaly of the lymphatic system. It is characterized by cystic lesions predominantly in the fetal neck and its prenatal diagnosis has been associated with increased perinatal mortality, aneuploidy, and congenital malformations.